AN ANALYSIS OF STUDENTS’ INDONESIAN-ENGLISH TRANSLATION OF DYSPHEMISM AND EUPHEMISM EXPRESSION ON ONLINE NEWS TEXT - Sabila Auliatun Nisa; Eline Rozaliya Winarto; Susilawati Susilawati (National Conference on Language, Education, and Technology Proceeding, 2022)
The aim of this research is to find out the forms and meaning changes of dysphemism and euphemism expression on online news text used in Indonesian-English translation. This research is a qualitative descriptive study and document analysis used as the instrument. The participant in this research was nine students of 6th semester of English Education Department at Universitas Muhammadiyah Cirebon in the academic year of 2022/2023. Data collection was collected with documents students’ translation result in translating online news text. The results showed that five euphemisms were found, namely colloquial, jargon, understatement, hyperbole, circumlocution and one for one substitutions. Meanwhile, the forms of dysphemism found were IST dysphemism (racist) and Derogatory or Disrespectful Terms Invoking Contempt for the Character Intended. This research also shows that euphemism and dysphemism experienced meaning changes. Keywords: dysphemism; euphemism; translation;